Research Note: Evaluating the vertical transmission potential of Salmonella Reading in broiler breeders - Abubakar Shitu Isah; Reshma Ramachandran; Anuraj Theradiyil Sukumaran; Aaron S. Kiess; Claudia D. Castañeda; Tim Boltz; Kenneth Macklin; Hossam Abdelhamed; Li Zhang (Poultry Science)
ABSTRACT: Salmonella Reading (S. Reading) recently emerged as a foodborne pathogen causing extensive human outbreaks in North America from consuming contaminated poultry products, mostly from turkeys. Understanding the transmission dynamics of this pathogen is crucial for preventing future outbreaks. This study investigated the ability of S. Reading to colonize the tissues and contaminate eggs of broiler breeders. We utilized 2 S. Reading strains, marked with bioluminescence gene: the outbreak strain RS330 and a reference strain RS326. We used 32 commercially sourced broiler breeder hens, 34 wk of age, randomly assigned to the 2 treatments (16 hens per strain). Each hen was intravaginally inoculated with 108 CFU of the respective strain on d 1 and was rechallenged on d 4. Eggs were collected daily postchallenge to recover bioluminescent S. Reading strains from the external eggshell surface and internal egg contents. On d 7 postchallenge, 10 hens from each treatment group were euthanized. Ovaries, oviducts, and ceca were aseptically collected to detect S. Reading colonization. Results showed that 70.5% (36 of 51) and 34.5% (19 of 55) of external eggshell surfaces, and 4.0% (2 of 50) and 1.8% (1 of 54) of the internal egg contents tested positive for the outbreak and nonoutbreak strains. Additionally, 40.0% of ovaries, 70.0% of oviduct, and 70.0% of ceca samples from the outbreak strain group, and 20.0% of ovaries, 70.0% of oviduct, and 80.0% of ceca samples from nonoutbreak strain group were positive. No significant difference (P = 0.05) was observed in all the findings among the strains except for the eggshell surface contamination. These findings suggest that S. Reading can effectively colonize reproductive tissues, translocate to the ceca, and contaminate the eggs of hens. Future research is needed to determine whether S. Reading can remain viable within the eggs throughout incubation and until hatching.